Examining the association between vigilance and mind wandering - Schwartzman, Brooke; Zanesco, Anthony P.; Denkova, Ekaterina; Tsukahara, Jason S.; Jha, Amishi P. (Frontiers in Cognition, 2025)
There has been a growing interest in the relationship between the vigilance decrement, characterized by performance decline with greater time-on-task, and the occurrence of mind wandering—task-unrelated thought. Recent evidence from a large-scale military sample suggests a link between performance declines and increased mind wandering over a 20-min Sustained Attention to Response Task. Herein, we examined if similar patterns are present when the task duration is shorter and delivered online to college students who rely on sustained attention for academic success. Specifically, we explored the relationship between the vigilance decrement and mind wandering in undergraduates (N = 310) completing a 10-min Sustained Attention to Response Task embedded with mind wandering probes. Bivariate growth curve modeling was used to examine within-task changes in performance and mind wandering over time-on-task as well as their covariance. The results revealed that a decrease in accuracy and an increase in response time variability were associated with an increase in mind wandering with greater time-on-task. In addition, self-reported task motivation, interest, and difficulty ratings were assessed as potential person-level moderators of changes with time-on-task. The results showed that individuals with higher motivation and interest ratings demonstrated a reduced time-on-task effect on response time variability and mind wandering. These findings suggest that mind wandering contributes to the vigilance decrement, even in shorter-duration tasks. Additionally, higher task-related motivation and interest appear to reduce the performance costs of mind wandering.